Identification of Molecular Integrators Shows that Nitrogen Actively Controls the Phosphate Starvation Response in Plants. Issue 5 (14th March 2019) - Medici, Anna; Szponarski, Wojciech; Dangeville, Pierre; Safi, Alaeddine; Dissanayake, Indeewari Madhubhashini; Saenchai, Chorpet; Emanuel, Amélie; Rubio, Vicente; Lacombe, Benoît; Ruffel, Sandrine; Tanurdzic, Milos; Rouached, Hatem; et al.
Abstract : Identification of molecular integrators shows that nitrogen actively controls the phosphate starvation response in plants. Abstract: Nitrogen (N) and phosphorus (P) are key macronutrients sustaining plant growth and crop yield and ensuring food security worldwide. Understanding how plants perceive and interpret the combinatorial nature of these signals thus has important agricultural implications within the context of (1) increased food demand, (2) limited P supply, and (3) environmental pollution due to N fertilizer usage. Here, we report the discovery of an active control of P starvation response (PSR) by a combination of local and long-distance N signaling pathways in plants. We show that, in Arabidopsis ( Arabidopsis thaliana ), the nitrate transceptor CHLORINA1/NITRATE TRANSPORTER1.1 (CHL1/NRT1.1) is a component of this signaling crosstalk. We also demonstrate that this crosstalk is dependent on the control of the accumulation and turnover by N of the transcription factor PHOSPHATE STARVATION RESPONSE1 (PHR1), a master regulator of P sensing and signaling. We further show an important role of PHOSPHATE2 (PHO2) as an integrator of the N availability into the PSR since the effect of N on PSR is strongly affected in pho2 mutants. We finally show that PHO2 and NRT1.1 influence each other's transcript levels. These observations are summarized in a model representing a framework with several entry points where N signal influence PSR. Finally, we demonstrate that this phenomenon is conserved in rice ( Oryza sativa ) and wheat ( Triticum aestivum ), opening biotechnological perspectives in crop plants.